Mercy and the structures of the world: Third Hans Singer Memorial Lecture - Stephen Chan Obe (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The Third Hans Singer Memorial Lecture by Stephen Chan on “Mercy and the Structures of the World” was an effort to sketch a moral equivalent to the broad thrust of the Singer-Prebisch approach to the economic universe. It cannot be as elegant or exact. There is no successful modelling of a moral universe that has been contentious since its first imagination. That last word is itself key: the economic universe has a conception, and the moral universe is imagined – even if afterwards rendered in conceptual languages. The lecture proceeded by way of four propositions: What might, in this argument, be called `poor' countries cannot assert the value of their philosophies, religious and political beliefs, or thought processes when, all the time, the response of `rich' countries – `rich' being applied to both economic and geopolitical structures of dominance – is to retain and expand the hegemonic nature of their own philosophies and beliefs. There is an irony here in that, very often, the philosophies of `poor' countries are richer in history, generations of re-imagination and refinement, with multiple paradigm shifts and complex contentions, than those of `rich' countries – and have, in some cases, been the guardians and transmitters of what the `rich' now take as their own. The philosophies of the `poor' have more `manufacture' within them than those of the `rich' whose dominance is set within a project of increase. However, even so, precisely because there is contention and identifiable histories – not sufficient to render the fabled `clash of civilisations', but sufficient to render perceptible differences which require transaction by debate without the guarantee of agreement – it may be argued that the moral universe, albeit with one dominant structure, has within it several discrete and contentious structures. The dominant structure nevertheless seeks to marshal differences according to its own preferences and convenience and, in a world of great economic and social inequalities, hegemonically rations mercy. The enlightened struggle of those within all structures is to work towards the equality of different philosophical and cultural structures, while seeking to `manufacture' as many interim mercies of as comprehensive and unrationed a nature as possible. What is profoundly required in views of the world, and actions in the world today is, therefore, the moral duty of imagination to seek equality without uniformity, commonality without universalism, and mercy without preconditions.
Keywords: 330